Associations Between Using Chinese Herbal Medicine and Long-Term Outcome Among Pre-dialysis Diabetic Nephropathy Patients: A Retrospective Population-Based Cohort Study - Guo, Jenny Chun-Ling; Pan, Heng-Chih; Yeh, Bo-Yan; Lu, Yen Chu; Chen, Jiun-Liang; Yang, Ching-Wei; Chen, Yu-Chun; Lin, Yi-Hsuan; Chen, Hsing-Yu (Frontiers in Pharmacology, 2021)
Background: Chronic kidney disease (CKD) has become a worldwide burden due to the high co-morbidity and mortality. Diabetic nephropathy (DN) is one of the leading causes of CKD, and pre-dialysis is one of the most critical stages before end-stage renal disease (ESRD). Although Chinese herbal medicine (CHM) use is not uncommon, the feasibility of using CHM among pre-dialysis DN patients remains unclear. Materials and methods: We analyzed a population-based cohort, retrieved from Taiwan’s National Health Insurance Research Database, to study the long-term outcome of using CHM among incident pre-dialysis DN patients from January 1, 2004, to December 31, 2007. All patients were followed up to 5 years or the occurrence of mortality. The risks of all-cause mortality and ESRD were carried out using Kaplan-Meier and competing risk estimation, respectively. Further, we demonstrated the CHM prescriptions and core CHMs using the Chinese herbal medicine network (CMN) analysis. Results: A total of 6,648 incident pre-dialysis DN patients were analyzed, including 877 CHM users and 5,771 CHM nonusers. With overlap weighing for balancing all accessible covariates between CHM users and nonusers, we found the use of CHM was associated with lower all-cause mortality (0.22 versus 0.56; log-rank test: p-value < 0.001), and the risk of mortality was 0.42 (95% CI: 0.36-0.49; p-value < 0.001) by adjusting all accessible covariates. Further, the use of CHM was associated with a lower risk of ESRD (cause-specific hazard ratio: 0.59, 95%CI: 0.55-0.63; p-value <0.001). Also, from the 5,901 CHM prescriptions, we found Ji-Sheng-Shen-Qi-Wan, Astragalus mongholicus Bunge or (Astragalus membranaceus (Fisch.) Bge.), Plantago asiatica L. (or Plantago depressa Willd.), Salvia miltiorrhiza Bunge, and Rheum palmatum L. (or Rheum tanguticum (Maxim. ex Regel) Balf., Rheum officinale Baill.) were used as core CHMs for different CHM indications and use of core CHMs was associated with a lower risk of mortality compared with CHM users without using core CHMs. Conclusions: The use of CHM seemed feasible among pre-dialysis DN patients; however, the beneficial effects still need to be validated by well-designed clinical trials.